Analysis of nonlinear heat exchange phenomena in natural convection cooled electronic systems. (December 2016) - De Mey, Gilbert; Torzewicz, Tomasz; Kawka, Piotr; Czerwoniec, Andrzej; Janicki, Marcin; Napieralski, Andrzej
Abstract: Thermal simulations of electronic systems usually are carried out employing linear models whose element values do not depend on temperature. The hypothesis on system linearity can be verified in practice by the summation of measured heating and cooling curves. When a considered problem is linear, at all time instants the curves always add up to the straight line corresponding to the steady state temperature value. However, the experiments carried out for a natural convection cooled power device with a heat sink showed that the temperature dependence of the heat transfer coefficient results in the appearance of a characteristic hump in this curve. A simple analytical model was developed here to predict the location of this extremum. The analyses presented in this paper are valid when the thermal time constant reflecting the thermal capacitance of a heat sink and the heat exchange with ambient is dominant. Highlights: Variation of structure surface temperature noticeably influences thermal resistance in natural convection cooled electronic. Perturbation theory can be used to explain nonlinear effects. Thermal time constant reflecting the heat exchange with ambient can be determined from the sum of heating and cooling curves.